2005
DOI: 10.1002/jor.20015
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity pulsed ultrasound accelerated bone remodeling during consolidation stage of distraction osteogenesis

Abstract: Bone regeneration in distraction osteogenesis occurs under tensile stress with axial rhythmic distraction after osteotomy. In this study, we evaluated if the low intensity pulsed ultrasound (LIPUS) was also effective on enhancement of bone remodeling during consolidation stage of distraction osteogenesis. Open osteotomy of seventeen 18-week-old female New Zealand rabbit tibiae were performed. The distraction was applied with the rate of 1 mm per day. LIPUS (30 mW/cm 2 , 1.5 MHz) was delivered for 20 min per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 46 publications
4
42
0
1
Order By: Relevance
“…EL-BIALY et al evaluated the effect of LIPUS on mandibular DO in rabbits and found a positive effect from LIPUS 8 . Compared with animal studies of LIPUS on long bone DO, the present findings are consistent with SHIMAZAKI et al 19 , SAKURAKICHI et al 17 , CHAN et al 2 and CHAN et al 1 in their conclusion of the effective timing of LIPUS, and similar to MAYR et al 14 , MACHEN et al 13 , EBERSON et al 7 and CLAES et al 5 , which demonstrated the positive effect of LIPUS.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…EL-BIALY et al evaluated the effect of LIPUS on mandibular DO in rabbits and found a positive effect from LIPUS 8 . Compared with animal studies of LIPUS on long bone DO, the present findings are consistent with SHIMAZAKI et al 19 , SAKURAKICHI et al 17 , CHAN et al 2 and CHAN et al 1 in their conclusion of the effective timing of LIPUS, and similar to MAYR et al 14 , MACHEN et al 13 , EBERSON et al 7 and CLAES et al 5 , which demonstrated the positive effect of LIPUS.…”
Section: Discussionsupporting
confidence: 95%
“…Several authors have reported the positive effects of LIPUS on long bone DO 2,17,19 . Few studies have evaluated the effect of LIPUS on membranous bone DO.…”
mentioning
confidence: 97%
“…Many attempts have been made to shorten the bone consolidation period during DO, including low-intensity pulsed ultrasound, 25 recombinant growth hormone, 26 intermittent parathyroid hormone, 27 calcitonin and alendronate, 28 calcium sulfate, 29 and growth factors such as BMPs and IGF. 30,31 In the present study, locally applied hNGFb accelerated callus maturation of a distraction gap in a rabbit mandibular distraction model.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,21,23,31,33,50,57,65,72,75,85 Pulsed US treatment also increases the rate of bone formation in distractions. 11,24,25,68,79 Exposure to low-intensity pulsed US (1.5 MHz, 30 mW/cm 2 ) for 20 min a day resulted in a 36% acceleration in the healing rate of distal radial fractures 44 and a reduction in the healing time of tibia fractures from 154 to 96 days. 35 Despite such well documented examples of accelerated and augmented fracture healing associated with low-intensity pulsed US treatment, the physical and biological process through which pulsed US interacts with living tissue remains unknown.…”
Section: Introductionmentioning
confidence: 99%